Gas-Sensing Performance of TiO2 Nanorod Arrays Synthesized by Solvothermal Method - Hersh Ahmed Khizir (Zanco Journal of Pure and Applied Sciences, 2025)
In this study, titanium dioxide (TiO₂) nanorods formed through by solvothermal growth on a glass substrate coated with FTO (fluorine-doped tin oxide) are synthesized in order to fabricate an Al/TiO₂-based gas sensor. This is valuable due to the morphology and nanostructure of the sensing film have an important effect on gas sensors' abilities for operation. Investigation using XRD and FESEM demonstrated the synthesized TiO2 nanorods' crystal nanostructure. Perfectly ordered and uniform TiO2 nanorods synthesized in an aqueous solution by varying the volumetric ratio of HCl to Ethanol and the acidity. At room temperature, the current–voltage (I–V) characteristic and the sensor's sensitivity to various reducing (ethanol and methanol) and oxidizing (oxygen, and carbon monoxide) gases were studied. For O2, CO, methanol, and ethanol gases, the corresponding relative sensitivity (Response) to a bias voltage (V) of 0.5 V is 53.758, 91.248, 108.298 and 144.689 %. While the gas sensor was in the dark and at room temperature, it was more sensitive to ethanol than other gases with good response and stability by the relative deviation of the gas response sensitivity was less than 2%. As a result, when compared to oxygen, carbon monoxide, and methanol gases, which have strong response sensitivity and stability, the study shows that TiO2 nanorods are a suitable method of enhancing ethanol sensing abilities.